Architecture of cloud platform for CAE simulation in supercomputing environment. (2016) - Deng, Ziyun; Zhang, Jing; Yin, Hanfeng
In order to design the architecture for the cloud platform for computer aided engineering (CAE) simulation, this paper presents the three layers to technical architecture, including user interaction layer, middleware layer, and high performance computing (HPC) resource layer. The platform adopts a series of security technology solutions in each layer. A technology called CAE application packaging template (CAE-APT) is proposed for integrating heterogeneous CAE software to make full use of the computing resources of 'Tianhe No. 1'. The platform has been implemented using the Java language, Tuscany, Struts, Hibernate, Spring and other open source software. According to the architecture, the design ideas and the key technologies in this paper, the second prototype of the platform has been completed, and the part applications in the platform have been demonstrated. The submission process of parallel computing about Mars exploration airbag illustrates the design thoughts of the platform.